Symbolic characters and class struggles in Ngugi’s wa Thiongo’s Petals of Blood - Stanley Ordu (Journal of Social, Humanity, and Education, 2022)
Purpose: Every piece of art must, without a doubt, make a statement about itself. This is due to the fact that the more attractive something is, the more symbolic it becomes. Almost all works of art have multiple interpretations. Every great work of literature contains symbols, which add depth, meaning, strength, and dexterity to the work. Research methodology: Two theoretical frameworks, postcolonial and Marxist literary theories, guided the analysis. And this is a qualitative study. Results: The results of this investigation demonstrate that colonial injustice and unmodified colonial institutions and policies are the most enduring issue of Ngugi Wa Thiong’o’s literary exploitation. Limitations: The study is limited to one novel and which is Petals of Blood of Ngugi Wa Thiong’o, written after the post-independence of Kenya. Contribution: Finally, the study found that people are aware of their rulers' actions and are plotting a revolt to break free from the elite's grasp. And it proposes viable answers to their political and socioeconomic problems, such as revolution, not just in Kenya but throughout Africa.